The haem‐uptake gene cluster in Vibrio fischeri is regulated by Fur and contributes to symbiotic colonization - Alecia N. Septer; Yanling Wang; Edward G. Ruby; Eric V. Stabb; Anne K. Dunn (Environmental Microbiology, 2011)
Summary Although it is accepted that bacteria‐colonizing host tissues are commonly faced with iron‐limiting conditions and that pathogenic bacteria often utilize iron from host‐derived haem‐based compounds, the mechanisms of iron acquisition by beneficial symbiotic bacteria are less clear. The bacterium Vibrio fischeri mutualistically colonizes the light organ of the squid Euprymna scolopes . Genome sequence analysis of V. fischeri revealed a putative haem‐uptake gene cluster, and through mutant analysis we confirmed this cluster is important for haemin use by V. fischeri in culture. LacZ reporter assays demonstrated Fur‐dependent transcriptional regulation of cluster promoter activity in culture. GFP‐based reporter assays revealed that gene cluster promoter activity is induced in symbiotic V. fischeri as early as 14 h post inoculation, although colonization assays with the haem uptake mutant suggested an inability to uptake haem does not begin to limit colonization until later stages of the symbiosis. Our data indicate that the squid light organ is a low iron environment and that haem‐based sources of iron are used by symbiotic V. fischeri cells. These findings provide important additional information on the availability of iron during symbiotic colonization of E. scolopes by V. fischeri , as well as the role of haem uptake in non‐pathogenic host‐microbe interactions.